Pelatihan Meningkatkan Branding Melalui Implementasi Digital Marketing pada UMKM Aquascape (Aqua Menoreh Gallery) - Edi Saputra; Asfa Mutiara Ahmad Pabulo (Politeknik Kampar, 2024)
This community service aims to develop digital technology mastery for MSMEs in entrepreneurship. To provide branding strength and increase market share, it is necessary to implement the use of social media for MSMEs so that their businesses can grow. The community service methods used include preparation, implementation, and evaluation. The preparation steps consist of licensing, observation of obstacles, and preparation of materials. The implementation stage includes explanations and training for MSMEs. The last stage is the evaluation stage by assessing the understanding of MSMEs' knowledge about digital marketing and increasing sales. The material to be provided is related to the concept of marketing content, the use of digital marketing e-commerce applications through social media. The results of community service utilizing digital marketing can provide a positive contribution in optimizing marketing for Aquascape Menoreh Gallery MSMEs. Better understanding and skills for MSMEs in using social media are expected to have a sustainable impact on the growth and development of MSMEs